2011
DOI: 10.1007/s00296-011-1798-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of disease activity indices in Korean patients with rheumatoid arthritis

Abstract: The aim of this study is to examine the validity of the rheumatoid arthritis (RA), disease activity score (DAS), 28-C-reactive protein (CRP), the simplified disease activity index (SDAI), and the clinical disease activity index (CDAI) against the DAS28-erythrocyte sedimentation rate (ESR) and determine cut-off values for each tool in Korean patients with RA. A total of 223 RA patients were consecutively recruited from the Hanyang University Hospital for Rheumatic Diseases in Seoul, Korea. DAS28-CRP, SDAI, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…In our study, the cut‐off point for defining remission was increased in order to optimize results of the clinimetric indices; the literature tends to diminish cut‐off points, probably because the populations included in previous studies correspond to individuals with RA with predominantly high or moderate heterogeneous activity, as opposed to our population which was in remission or low activity. The other likely explanation is that the number of painful joints in our study is greater than in the populations published that are classified in remission; the painful joint count, ultimately, has a very important role in the equation of the clinimetric indices and substantially modifies the final result …”
Section: Discussionmentioning
confidence: 70%
“…In our study, the cut‐off point for defining remission was increased in order to optimize results of the clinimetric indices; the literature tends to diminish cut‐off points, probably because the populations included in previous studies correspond to individuals with RA with predominantly high or moderate heterogeneous activity, as opposed to our population which was in remission or low activity. The other likely explanation is that the number of painful joints in our study is greater than in the populations published that are classified in remission; the painful joint count, ultimately, has a very important role in the equation of the clinimetric indices and substantially modifies the final result …”
Section: Discussionmentioning
confidence: 70%
“…SDAI and CDAI have been validated in a number of studies from the west . While SDAI and CDAI have been validated individually in Indian patients, there is just one study which has compared both and has found good correlation with DAS‐28 .…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that DAS 28-CRP can be used as an alternative to DAS28-ESR. SDAI and CDAI are simple, effective measurements of disease activity in rheumatoid arthritis and are significantly correlated with DAS28 [23]. SDAI is easy to calculate and is a viable tool for day-today clinical assessments.…”
Section: Discussionmentioning
confidence: 99%